Virus Discovery Using Tick Cell Lines - Bell-Sakyi, Lesley; Attoui, Houssam (Evolutionary Bioinformatics, 2016)
While ticks have been known to harbor and transmit pathogenic arboviruses for over 80 years, the application of high-throughput sequencing technologies has revealed that ticks also appear to harbor a diverse range of endogenous tick-only viruses belonging to many different families. Almost nothing is known about these viruses; indeed, it is unclear in most cases whether the identified viral sequences are derived from actual replication-competent viruses or from endogenous virus elements incorporated into the ticks' genomes. Tick cell lines play an important role in virus discovery and isolation through the identification of novel viruses chronically infecting such cell lines and by acting as host cells to aid in determining whether or not an entire replication-competent, infective virus is present in a sample. Here, we review recent progress in tick-borne virus discovery and comment on the actual and potential applications for tick cell lines in this emerging research area.